32. Impact of a Four-Year Antimicrobial Stewardship Program on Antimicrobial Resistance. (4th December 2021) - Chrysou, Konstantina; Zarkotou, Olympia; Mamali, Vasiliki; Rekleiti, Nektaria; Themeli-Digalaki, Katina; Chrysos, Georgios; Tsakris, Athanasios; Pournaras, Spyridon
Abstract: Background: Antimicrobial resistance (AMR) is an increasing threat to public health and antimicrobial consumption is a primary driver of resistance. Many studies have shown that the implementation of an antibiotic stewardship program (ASP) improves prescribing of antibiotics and can reduce AMR. Purpose of the study was to assess the impact of a successful ASP, implemented for four years, on AMR in our 427-bed tertiary general hospital. Methods: We monitored pharmacy data for the years 2015 (pre-intervention) and 2016-2019 (post-intervention) for antibiotic consumption (DDD/100 bed-days) and resistance rates. AMR data were obtained from the clinical microbiology laboratory's electronic database. To achieve the goals of ASP we used a range of interventions as pre-authorization strategy for the protected antibiotics (tigecycline, carbapenems, quinolones, glycopeptides, daptomycin, colistin, linezolid), prospective audit and feedback with direct intervention, de-escalation or switch from iv to oral administration and appropriate selection and duration of chemoprophylaxis in surgery. Results: Significant reductions were observed for: total antibiotics, colistin, carbapenems, quinolones and tigecycline consumption during study period. Significantly lower resistance rates were documented in 2019 compared to 2015 for Pseudomonas aeruginosa and for Klebsiella pneumoniae . As for Acinetobacter baumannii isolates, which in our hospital are highly-resistant exhibiting >90% resistance to carbapenems, no significant changes were noted during the study period. Infections caused by Gram-positive pathogens are less prevalent in our hospital. Lower rates of vancomycin-resistant enterococci were noted after the implementation of our ASP (30.4% in 2019 vs. 50.0% in 2015 for E. faecium and 0.6% vs. 6% for E. faecalis, respectively), whereas methicillin-resistant S. aureus isolates increased (40% in 2019 vs. 31.1% in 2015), possibly because most of these infections were not hospital-acquired. Resistance rates of Pseudomonas and Klebsiella Conclusion: Our ASP was successful in reducing antibiotic consumption and AMR for important pathogens. Disclosures: All Authors : No reported disclosures